Integrationism and the Self - Hutton, Christopher (Taylor & Francis, 2023)
In recent years a set of challenging questions have arisen in relation to the status of animals; their treatment by human beings; their cognitive abilities; and the nature of their feelings, emotions, and capacity for suffering. This ground-breaking book draws from integrational semiology to investigate arguments around the rights of certain animals to be recognized as legal persons, thereby granting them many of the protections enjoyed by humans.